Empirical Analysis of Body Constitution and Food Intake in Persons with Type 2 Diabetes from a TCM Perspective - Wong, Peggy Yee-Chi; Pang, Samantha Mei-Che; Chan, Rose Yuk-Pui (Journal of Nutritional Therapeutics, 2014)
This study examined the correlations between body constitution (BC) and food intake in a sample of persons with Type 2 Diabetes (T2DM) from a perspective of traditional Chinese medicine (TCM). Past research on BC of persons with diabetes (DM) from a TCM perspective revealed imbalanced state of Yin and Yang in terms of Yin-deficiency (YID), Yang-deficiency (YAD), and Yin-Yang-deficiency (YYD). However, no studies have attempted to find out if daily food intake has an influence on Yin–Yang balance. The present study adapted a mixed method, which constituted of two phases. Phase one involved an exploratory case study (n=18) conducted between May and June 2011 and phase two, a descriptive correlation study (n=210) between October and December 2013. Results showed that in phase-one, three cases showed YID and higher food intake in hot/warm nature, 12 cases with YAD and higher food intake in cold/cool nature while three cases with Yin-Yang-deficiency (YYD) and extremely high food intake in cold/cool nature. In phase-two, Spearman’s correlation coefficient between food intake and YID presentations (YIDPs) (hot/warm food: rho=0.34, p=0.000; cold/cool food: rho= 0.18, p=0.006); YAD presentations (YADPs) (hot/warm food: rho=0.18, p=0.008; cold/cool food: rho=0.2, p=0.006); and YYD presentations (YYDPs) (hot/warm food: rho=0.29, p=0.006; cold/cool food: rho=0.2, p=0.003) have been noted. The findings concluded that persons with T2DM and YIDPs, YADPs, or YYDPs tend to have food intakes higher in hot/warm nature or cold/cool nature